Pengaruh Live Streaming Shopping dan Time Limit Terhadap Perilaku Impulsive Buying Pada Pembelian Online di Aplikasi Tiktokshop dalam Perspektif Bisnis Syariah : (Studi Pada Pengguna Tiktokshop di Kota Bandar Lampung) - Okta Supriyaningsih; Erlin Kurniati; Putri Susi Adetya (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
In promoting products at TikTok Shop there is Live Streaming which is the choice of many producers to make sales and direct interaction with consumers in real time. People's heavy dependence on gadgets causes the buying process to be easier through Live Streaming, so that it can lead to impulsive buying behavior. The formulation of the problem in this study is whether Live Streaming has a positive and significant effect on Impulsive buying? Does Time Limit have a positive and significant effect on Impulsive Buying? And how are Live Streaming, Time Limit and Impulsive Buying in a sharia business perspective? While the purpose of this study is to determine the effect of Live Streaming on Impulsive Buying behavior, to determine the effect of Time Limit on Impulsive Buying behavior and to find out how Live Streaming, Time Limit and Impulsive Buying in a sharia business perspective. This study uses quantitative research methods, the aim is to test a hypothesis that has been used. In this study using data collection techniques by distributing questionnaires to Tiktoktshop users in Bandar Lampung. The population in this study were people in Bandar Lampung City aged 17 years and over because considering these age conditions it is hoped that respondents can better understand the purpose of the questionnaire given. And the sample used in this study were 100 respondents. Based on the research that has been done, the results are in line with the hypothesis, where there is an influence from Live Streaming (X1) on Impulsive Buying (Y) positively and significantly. Meanwhile, Time Limit (X2) also has a positive and significant effect on Impulsive Buying (Y). So Live Streaming and Time Limit together have a positive and significant effect on Impulsive Buying.